Arc magma compositions controlled by linked thermal and chemical gradients above the subducting slab. Issue 11 (4th June 2013) - Watt, Sebastian F. L.; Pyle, David M.; Mather, Tamsin A.; Naranjo, José A.
Abstract [1] Global arc magmatism is sustained by a continuous fluid flux that is returned to the mantle in subduction zones. Despite considerable advances in simulations of melting processes, models of arc magmatism remain incompletely tested against erupted products. Here, we show that a suite of primitive volcanic rocks from across the southern Chilean arc preserves the signature of a systematic down‐slab gradient in fluid chemistry. The chemical gradient is consistent with predictions from modeling, geothermometry and experiments. We infer that increasing slab‐surface temperatures cause the sub‐arc slab flux to become less water‐rich and increasingly dominated by hydrous melts over a distance of a few kilometers behind the arc front. This change exerts a first‐order control on magma chemistry, and implies discrete melt‐transport pathways through subduction zones. Our results replicate patterns in other arcs, implying common sub‐arc slab‐surface temperature ranges in thermally‐diverse subduction zones.